CULTIVATING CORE COMPETENCIES FOR AGRICULTURAL HUMAN CAPITAL: THE ROLE OF INDUSTRY-EDUCATION INTEGRATION IN CHINA - Fang, Yinjie; Shi, Yijun (Journal of Economic Education, 2025)
This study investigates the core competencies of agricultural undergraduates in China, aiming to improve their skills through industry-education integration. Using human capital theory, it analyzes the current status via literature review, surveys, and interviews, focusing on L University. Findings show students recognize their field's importance but lack career confidence and practical experience; only 25.5% have internships, and few faculty have industry experience. Gaps in social skills and psychological resilience are noted. To enhance competencies, strategies include creating a pro-agriculture atmosphere, deepening industry-education ties, boosting comprehensive training, and innovating evaluation. The study builds a competency model, highlighting fixed and growth competencies, enriching agricultural education theory. It stresses industry-education integration to meet talent demands for agricultural modernization and points to the need for more research on integration evaluation and context-specific characteristics.